The inclusion ofEnvironmental concerns in the development of Biofuel Policies for Transport - Figueroa, Maria Josefina (Proceedings from the Annual Transport Conference at Aalborg University, 2009)
Biofuels are providing an increasing percentage of the transportation fuel in Europe. The reference value given for a potential expected market increase has been 5 % by the end of 2010, presumably half of this increase would need to be supplied by trade and international biofuel markets according to the European Commission. An important question that needs addressing is whether international trade on biofuels for transport can be developed in a way that is socially and environmentally sustainable. This paper attempts to provide an initial answer to this question. The paper provides a comparative review of the characterization and accounting of environmental impacts of biofuel production, distribution and consumption that informs the development of local policies and decisions about import/export capabilities in selected countries. The paper consists primarily on a summary report on the findings of a desk-study review of official national published reports, websites, and comparative international studies. The scope of the search considered general assessment on biofuels published in at least three European countries, international organizations and a couple of other main biofuel producer/consumers (US, Brazil). The findings are grouped in categories: regarding the assumptions and emphasis given in each country/study, listing the environmental implications considered and the development of frameworks to handle the sustainability impacts of biofuel production. The results seek to highlight critical findings and compare diverse policy development in terms of areas of emphasis, emerging concepts, use of frameworks for analysis of environmental impacts, setting of targets and conditions for sustainability. The study reveals that significant uncertainty remains in methodologies and factors used to assess environmental impacts.– including calculations of GHG and energy balances. Further development of the life-cycle assessment tool for biofuels is essential specifically to give greater attention to subjects such as human, social and ecological health, biodiversity and land changes, all of which need to be featuring as prominently in the assessment as the concerns about climate change and resource depletion. The need for the emergence of new institutions at the local level that can give credibility to monitoring efforts and global implementation of stringent sustainability standards for biofuel production, distribution and consumption appears to be one of the greatest and more difficult challenges that needs addressing.